2020
DOI: 10.1038/s41580-019-0199-y
|View full text |Cite|
|
Sign up to set email alerts
|

mTOR at the nexus of nutrition, growth, ageing and disease

Abstract: The mTOR pathway integrates a diverse set of environmental cues, such as growth factor signals and nutritional status, to direct eukaryotic cell growth. Over the past two and a half decades, mapping of the mTOR signalling landscape has revealed that mTOR controls biomass accumulation and metabolism by modulating key cellular processes, including protein synthesis and autophagy. Given the pathway's central role in maintaining cellular and physiological homeostasis, dysregulation of mTOR signalling has been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
1,765
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,746 publications
(1,949 citation statements)
references
References 291 publications
29
1,765
0
10
Order By: Relevance
“…Intriguingly, glucose deprivation-induced ULK1 phosphorylation is in part AMPK dependent and previous studies showed that ULK1 is a target of both AMPK and mTORC1 (refs. 2,27 ). Nevertheless, it is still not clear how ULK1 senses glucose starvation 28 .…”
Section: Ulk1 and The Trna Synthetase Lars1mentioning
confidence: 99%
“…Intriguingly, glucose deprivation-induced ULK1 phosphorylation is in part AMPK dependent and previous studies showed that ULK1 is a target of both AMPK and mTORC1 (refs. 2,27 ). Nevertheless, it is still not clear how ULK1 senses glucose starvation 28 .…”
Section: Ulk1 and The Trna Synthetase Lars1mentioning
confidence: 99%
“…TOR signalling is a key amino acid signalling pathway that is critical for growth, reproduction and lifespan. Because TOR activity increases with dietary protein levels, it has been implicated as mediating the detrimental effects on lifespan of high protein diets (Liu & Sabatini, 2020). This is supported by the fact that rapamycin, a pharmacological suppressor of TOR, has been shown to extend lifespan across numerous species, including Drosophila where it also suppresses egg production (Bjedov et al, 2010;Schinaman, Rana, Ja, Clark, & Walker, 2019;ScialĂČ et al, 2015).…”
Section: Lifespan Extension By Rapamycin Depends On Dietary Cholestermentioning
confidence: 99%
“…5e). We them focused our attention on the two best-characterized mTORC1 targets, the ribosomal protein S6 [downstream target of the serine/threonine kinase p70S6K1 (S6K1)], and the eIF4Ebinding protein 1 (4E-BP1) [50,51]. Levels of phosphorylated form of S6 at S240/244 were increased in control group in TA muscle, but this effect was signi cantly lower in obestatin-treated animals (Fig.…”
Section: Resultsmentioning
confidence: 99%